Bentuk-Bentuk Pelelintangan Di Sanggar Wasundari Desa Kamasan Sebagai Sumber Inspirasi Seni Lukis - Sudana, I Made; Putra, I Gusti Ngurah; Yugus, A.A Gede (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
The illustration of pelelintangan is traditional astronomical knowledge that contains information about the prediction of a person's character/personality and fate according to the day of birth. The illustration of pelelintangan is usually presented in the classic form of Kamasan wayang painting. This can be seen in the work of I Nyoman Mandra (late) in the Wasundari Studio. Pelelintangan is basically just a picture of human life which is a prediction and is not absolute or uncertain truth. The creation process is carried out using primary data collection methods such as; interviews and observations, and secondary data collection methods such as reading, documentation, and the internet. The dissected uses several theories such as semiotic theory and aesthetic theory. The problems of this creation are (1) How to visualize the shapes and motifs of the painting in the painting? (2) What is the technique of visualizing the cross-sectional theme on canvas media? (3) What meanings are contained in passing? The purpose of this research and creation of art is to find out visual language, illustration of pelelintangan and their relationship with character/personality by birth and to create six types of works inspired by the shape of pelelintangan